Catalogue des peintures françaises. - Koenig, Léon; Musée des Beaux-Arts, Liège (Liège : Musée des Beaux-Arts, 1963)
Abel-Truchet ; Adnet, France ; Aizpiri, Paul ; Andre, Jules ; Arp, Jean ; Taeuber, Sophie ; Beraud, Jean ; Bergeret, Pierre ; Blanc, Charles ; Blanchard, Maria ; Bordier du Bignon, Jacques ; Boudin, Eugène ; etc.
boek